2010
DOI: 10.1159/000308361
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Traditional NSAID-Induced Small Intestinal Injury: Recent Preliminary Studies Using Capsule Endoscopy

Abstract: Capsule endoscopy and balloon endoscopy, advanced modalities that now allow for full investigation of the entire small intestine, have revealed that non-steroidal anti-inflammatory drugs (NSAIDs) can cause a variety of abnormalities in the small intestine. Traditional NSAIDs can induce small intestinal injuries in over 50% of patients. Several studies have shown that the preventive effect of proton pump inhibitors does not extend to the small intestine, suggesting that concomitant therapy may be required to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
0
16
0
3
Order By: Relevance
“…However, in the majority of patients, LDA is used as an antiplatelet agent and cannot be discontinued due to the increased risk of cardiovascular or cerebrovascular morbidity and mortality. Thus far, several studies have been conducted on the prevention and treatment regimens of NSAID-induced small-bowel mucosal injury [20,21,26,27,28,31,32,36,37,38,39,40]. Fujimori et al [26] have shown that rebamipide is effective for reducing the incidence of diclofenac-induced small intestinal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the majority of patients, LDA is used as an antiplatelet agent and cannot be discontinued due to the increased risk of cardiovascular or cerebrovascular morbidity and mortality. Thus far, several studies have been conducted on the prevention and treatment regimens of NSAID-induced small-bowel mucosal injury [20,21,26,27,28,31,32,36,37,38,39,40]. Fujimori et al [26] have shown that rebamipide is effective for reducing the incidence of diclofenac-induced small intestinal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Many capsule endoscopic studies for healthy volunteers revealed that the concomitant administration of COX non-selective NSAIDs and proton pump inhibitor (PPI) can induce small intestinal mucosal injuries in over 50% of study subjects [6]. Hence, small intestinal mucosal injury is not infrequent with the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, NSAID-induced small intestinal lesions have drawn particular attention recently as a result of the development of the capsule endoscope and double-balloon endoscope [3,4,5,6]. These techniques have enabled the identification of previously undetectable lesions in the human small intestine and demonstrated that such lesions are more common than previously thought.…”
Section: Introductionmentioning
confidence: 99%